Biomateriais à base de quitosana de camarão e bactérias para remoçao de metais traços e petróleo - Carvalho, Técia Vieira (2006)
As the environmental problems caused by the impacts of industrial activities increase the man tries to improve or to develop new descontamination techniques. The bioremediation stands out for a wide range of microorganisms that can metabolize many of the pollutants, besides not leaving residues or recalcitrant by-products, as it usually happens with other techniques. One of the most recent innovations in this concern is the use of immobilized microorganisms. The immobilization has many advantages besides facilitating the control of the process and the microorganisms. The chitosan, a natural polysaccharide that can be obtained from crustacea shells, presents several characteristics that turn it an ideal support for immobilization of certain microorganisms such as its biodegradability, lipofilic properties, capacity to form gel and beads and it can be reticulated. In this work was prepared a chitosan starting from chitin of shrimp shells with degree of desacetilation of 78% and molar mass of 117.000 Da. This polymer was used for immobilization of the Staphylococcus saprophyticus subsp. saprophyticus strain, selected by the cell-wall hydrophobicity, what turns it an emulsificant. Beads, membranes, films and hydrogels were produced with and without immobilized bacteria. The products were tested for oil-water emulsification, removal of copper and lead from contaminated water and as clotting of oil in water. The products were also available for the mechanical resistance, uniformity, solubility and analyzed by electronic microscopy of varredure. The results showed that the incorporation of the bacteria into chitosan improved significantly the resistance of this polymer. The chitosan membrane supported up to 53.62 Mpa while a similar membrane containing immobilized bacteria supported up to 73.96 Mpa. The beads with the bacterium also stood out for the uniformity and mechanical resistance during the tests of oil-water emulsification. The beads with cells unlike the beads without cells promoted the hydrocarbon emulsification, reaching of 60%. The films obtained by the treatment of the membranes with glycerol 20% behaved very different far from the membranes. The films were less resistant to traction, supporting 20.50 Mpa and 8.91 Mpa, for films without cells and with cells respectively. On the other hand, the films were significantly more elastic than the membranes, as proven by the values of the Young modules, 146.4 Mpa and 222.8 Mpa, for films without cells and with cells, respectively. The membranes with immobilized bacteria removed copper and lead more efficiently than the membranes without cells, while the films showed the same result independently of having or not immobilized cells. Both films were impermeable to the passage of copper and lead solutions. The beads containing cells were significantly more efficient for metal adsorption from samples of polluted waters. Comparatively, the copper was better adsorpted than the lead. There were not observed any difference on the removal of 200 μg/g of copper and lead that should be attributed to the differences of fresh and sea water. The copper and lead adsorption was of 20mg/g of chitosan while the desorption was more than 90% for the copper and more than 80% for the lead. No differences were observed among the petroleum coagulation spilled in water with chitosan gels with or without cells. In conclusion, the products developed and tested in this work showed great potential for bioremediation applications.